The Contextual Teaching Learning Approach and the Buddhayana Spirit Movement: Implementation of Picture Story Learning Media "Buddha's Biography" in Chinese Language Learning - Nuriani, Nuriani (Journal of Education, Religious, and Instructions (JoERI), 2024)
The Contextual Teaching and Learning (CTL) approach has become the focus in the Buddhist lecture process so that students can apply Buddhism in all aspects of life. This CTL approach is in line with the principles of Applied Buddhism and the Buddhayana Spirit Movement which are two important aspects of Buddhist life. This study aims to apply the CTL approach in the context of Chinese courses to STAB Bodhi Dharma students, using the learning media of picture stories "Buddha's Biography." Classroom Action Research Methods are used to develop this research through a cycle of problem diagnosis, action design, action execution and observation, data analysis, evaluation and reflection. Efforts to apply Buddhism in student life through Chinese courses with learning media for picture stories "Buddha's Life History" have succeeded in integrating understanding Chinese with Buddhist values and teachings. The results showed that through this learning medium, students not only gained Chinese language skills, but also understood the values of Buddhist life that can be applied in daily life and become part of efforts to develop the Buddhayana Spirit Movement.